2019
DOI: 10.2147/ccid.s201012
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hearing status in patients with vitiligo</p>

Abstract: Background: Vitiligo is an acquired disorder characterized by depigmented macules and patches that result from a progressive loss of functional melanocytes. During embryogenesis, precursor cells of melanocytes (melanoblasts) migrate not only to the epidermis and hair follicles but also to the leptomeninges, uveal tract of the eye, and inner ear. Thus, it has been proposed that these organs may be involved in vitiligo, as well. Objective: This study was designed to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Considering that melanin pigment protects the inner ear against oxidative stress, ototoxic drugs, and high noise exposure, the inability to cope with prolonged stress might explain the relationship between disease duration and hearing loss. However, other studies have found no significant relationship between disease duration and hypoacusis 9,11,18 . Variation among studies in mean disease duration may be a factor affecting these results.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Considering that melanin pigment protects the inner ear against oxidative stress, ototoxic drugs, and high noise exposure, the inability to cope with prolonged stress might explain the relationship between disease duration and hearing loss. However, other studies have found no significant relationship between disease duration and hypoacusis 9,11,18 . Variation among studies in mean disease duration may be a factor affecting these results.…”
Section: Discussionmentioning
confidence: 72%
“…Studies assessing hearing in vitiligo patients by conventional audiometry have yielded conflicting results. Some studies have found no significant relationship between vitiligo and hearing loss 10,11 . AlGhamdi et al 10 attributed this to the lower average age of the patients in their study group (mean, 23.21 years) compared with other studies.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The produced melanin is further distributed to neighboring keratinocytes and to hair follicles. Melanin is also present in other body sites, including the eye, inner ear, meninges, and the substantia nigra in the brain [10][11][12][13][14] . Vitiligo occurs because of the marked reduction of melanocytes in affected skin areas.…”
Section: Introductionmentioning
confidence: 99%